P–465 Effect of letrozole over Ki–67 expression in breast cancer during controlled ovarian stimulation (COS) for fertility preservation (FP): case report. (6th August 2021) - Vanni, V S; Cioffi, R; Bergamini, A; Sarais, V; Signorelli, S; Corti, L; Papaleo, E; Candiani, M; Mangili, G
Abstract: Study question: Does concomitant letrozole administration during COS alter Ki–67 expression in women undergoing FP procedures before breast cancer surgery? Summary answer: Concomitant letrozole administration during COS, even for a short period, can reduce Ki–67 expression in breast cancer. What is known already: The biggest concern with COS in breast cancer patients is the increase in serum estradiol levels, caused by the development of multiple follicles simultaneously. This has always been a major hindrance to the use of traditional ovarian stimulation regimens in these patients, due to the large amount of evidence on the pathogenetic role of estrogen in breast cancer propagation. To limit the rise of estradiol during COS, most centers have adopted concomitant letrozole administration. Recently, some studies have reported changes in tumor pathology after letrozole administration, such as a significant fall in Ki–67 expression. Study design, size, duration: Case report including 2 patients undergoing COS with concomitant letrozole administration for 12 days before breast cancer surgery. Participants/materials, setting, methods: The first patient was a 28-year-old Caucasian woman with a breast biopsy showing an infiltrating ductal carcinoma in the upper external quadrant of the right breast. The second patient was a 33-year-old Caucasian woman with a diagnosis of infiltrating ductal carcinoma of the upper external quadrant of the left breast. Both patients underwent COS with concomitant letrozole administration 5 mg daily for 12 days. Ovarian stimulation was performed using a GnRH-antagonist random-start protocol. Main results and the role of chance: In the first patient, Ki–67 expression in the initial biopsy was 55%. After completion of FP procedures, she underwent quadrantectomy with sentinel-lymphnode biopsy. In the final histopathological report Ki–67 expression fell to 25%. In the second patient, the first biopsy showed a Ki–67 expression of 30%, while after mastectomy it fell to 10%. Limitations, reasons for caution: Only 2 patients were included in the study. Wider implications of the findings: COS is feasible before breast cancer surgery, as long as an adequate cancer biopsy with immunohistochemical evaluation has been collected. Cytological diagnosis is not enough to start FP procedures. Evaluation of biological parameters after letrozole administration could lead to underestimation of cancer proliferation rate and to inappropriate treatment strategies. Trial registration number: NA